Cancer and atrial fibrillation/flutter: an analysis of patients referred to electrical cardioversion. (14th October 2021) - Menezes Fernandes, R; Mota, T.F; Costa, H.A; Espirito Santo, M; Bento, D; Candeias, R; Mimoso, J; Jesus, I
Abstract: Introduction: Cancer is associated with an increased risk of atrial fibrillation (AF) development. Both an active tumour and AF are related to increased thromboembolic risk. Purpose: To determine the clinical characteristics, management and prognosis of cancer patients with AF or atrial flutter (AFL) referred to electrical cardioversion (EC). Methods: We conducted a retrospective study encompassing patients referred to EC due to AF/ AFL in our Cardiology Department, from September 2011 to September 2020. Clinical characteristics, echocardiographic studies and follow-up data were analysed. We considered patients with a recent (up to 5 years) diagnosis of cancer. Primary endpoints were the occurrence of stroke, bleeding complications and all-cause mortality. Results: A total of 691 patients were included, with a median age of 67 years-old and 70, 8% male predominance. AFL was identified in 21, 1% of patients and 57, 4% had arterial hypertension. Persistent AF/AFL was diagnosed in 60, 7%, 20, 4% presented with first diagnosed AF/AFL and 17, 9% had paroxysmal episodes. 89, 5% of patients had indication for anticoagulation therapy and, of these, 75, 4% were medicated with non-vitamin K antagonist oral anticoagulants (NOAC). 58 patients (8, 4%) had a recent diagnosis of cancer, who were older (69, 7 vs 67, 9 years-old; p<0, 001) and more frequently cardioverted in an outpatient setting (63, 8%). They had a lower rate of heart failure (1, 9% vs 16, 7%; p=0, 004), but a higher prevalence of sleep apnea (13% vs 5, 4%; p=0, 025) and chronic kidney disease (10, 9% vs 4, 2%; p=0, 027). HAS-BLED score was applied, and higher values were obtained in cancer patients (1, 0 vs 0, 7; p=0, 002). CHA2DS2-VASc score was not significantly different between both groups. NOAC were preferred in cancer patients (86, 8% vs 74, 2%; p=0, 043), instead of vitamin K antagonists. These patients were less referred to AF/AFL ablation procedures (1, 9% vs 11, 6%; p=0, 027). During a median follow-up of 1342 days, no significant differences were found regarding the occurrence of ischemic stroke and bleeding complications. All-cause mortality was significantly higher in cancer patients (31, 5% vs 15, 5%; p=0, 003), but none died from cardiovascular causes. Conclusion: Cancer is frequent in patients with AF/AFL referred to EC, who are older and had a higher bleeding risk. Stroke rate was not significantly different than other patients, and NOAC seem to be a safe medication in this population. All-cause mortality is high in cancer patients, but we did not find any association with cardiovascular causes. Funding Acknowledgement: Type of funding sources: None.